Power and bandwidth efficiency of wireless mesh networks. Issue 3 (1st September 2013) - Zhao, Liqiang; Gao, Lu; Zhao, Xiaodong; Ou, Shumao
Abstract : As a prevalent network topology, mesh, has been actively researched and developed as a key solution to improve the performance and services of wireless communications. In this study, the authors carry out a comprehensive analysis of the bandwidth efficiency (BE) in b/s/Hz and power efficiency (PE) in b/s/Hz/W of carrier sense multiple access with collision avoidance, the basic medium access control protocol for wireless mesh networks (WMNs). Analysis results show that the suboptimal, not the maximal, power and BE can be achieved simultaneously under the same conditions, for example, the number of competing nodes and contention windows. Hence, the authors present a heuristic bandwidth‐PE tradeoff design. Simulation results show that the authors proposed protocol works well in both single‐hop and multi‐hop WMNs.